Атрибуція диктатури - Казанцева, С. С. (ХНУРЕ, 2023)
Historical examples show now dictatorial regimes use airrerent ways to secure their power. All of them have one strategic goal - to preserve the dictator's power, and an important tendency - to total control over society. The purpose of this study is to attribute the manifestations of a dictatorial regime through the analysis of its nature and features, mechanisms of its functioning and consequences for society. This work is devoted to defining the main ways of manifestation of dictatorship.